Writable and patternable organic solar cells and modules inspired by an old Chinese calligraphy tradition. Issue 1 (18th December 2017) - Mao, Lin; Luo, Bangwu; Sun, Lulu; Xiong, Sixing; Fan, Jiacheng; Qin, Fei; Hu, Lin; Jiang, Youyu; Li, Zaifang; Zhou, Yinhua
Abstract : A fabrication technique inspired by an old Chinese calligraphy tradition is developed to fabricate organic solar cells and modules. Abstract : Scalable, patternable and affordable thin-film fabrication techniques for solution-processed organic photovoltaics are highly desirable. In this work, we report a new fabrication technique inspired by an old Chinese calligraphy tradition to fabricate organic solar cells and modules. The fabrication tool of "Maobi", also called "Chinese ink brush", has over 2000 years of history and has been widely used for writing and painting in old Chinese history. Using Maobi coating, the thickness of the active layers and the polymer electrodes could be tuned by optimizing the coating speed and substrate temperature. Solar cells based on Maobi-coated active layers (P3HT:ICBA, PTB7-Th:PC71 BM and PBDB-T:ITIC) display comparable performance to the devices with spin-coated active layers. Among them, the cells with the Maobi-coated PBDB-T:ITIC active layer exhibit high power conversion efficiencies of 10.1%. Furthermore, based on the inherent advantage of the easy patterning of Maobi, we demonstrated Maobi-coated solar modules containing 8 sub-cells that exhibit a high open-circuit voltage ( V OC ) of 6.3 V and a high fill factor of 0.71. At the end, large-area solar modules (18 cm 2 ) were demonstrated via a motor-driven computer-controlled automatic Maobi coating. The module displays V OC of up to 11.6 V and a power conversion efficiency of 6.3%.